Recent family-group names (2013–2019) in the scale insects (Hemiptera: Sternorrhyncha: Coccomorpha) - Williams, D.j. (Zootaxa, 2020)
A list is provided of scale insect (Hemiptera: Sternorrhyncha: Coccomorpha) family-group names published between 2013 and the end of 2019. This is a supplement to two previous lists by Williams, covering names published from 1814–1968, and those published from 1969–2012. As in the previous lists, each entry is headed by the nominal genus on which each family‑group name is based followed by any new ranks.